Patient Use of Cost and Quality Data When Choosing a Joint Replacement Provider in the Context of Reference Pricing - Kandrack, Ryan (Health Serv Res Manag Epidemiol, 2015)
Health plans are encouraging consumerism among joint replacement patients by reporting information on hospital costs and quality. Little is known about how the proliferation of such initiatives impacts patients’ selection of a surgeon and hospital. We performed a qualitative analysis of semistructured interviews with 13 patients who recently received a hip or knee replacement surgery. Patients focused on the choice of a surgeon as opposed to a hospital, and the surgeon choice was primarily made based on reputation. Most patients had long-standing relationships with an orthopedic surgeon and tended to stay with that surgeon for their replacement. Despite growing availability of cost and quality information, patients almost never used such information to make a decision.